Collapse Potential of Loess under Unloading Effect - Xin Jin; Tie-Hang Wang; Zai-Kun Zhao; Liang Zhang; Yan-Zhou Hao (Advances in Civil Engineering)
Collapsible loess is generally characterized by a sudden and substantial decrease in volume that occurs when is applied under constant stress. To evaluate the loess collapse potential, the self-weight collapse and collapse coefficients have been defined by the code for building construction in collapsible loess regions. However, the method in the code does not account for the vertical stress variation. The loess collapse process commonly occurs with stress variation in practice. This paper documents a low-cost, quantitative evaluation scheme using regression analysis to evaluate the loess collapse potential by varying the unloading levels. The results show that the factors that prominently account for loess collapse deformation are the initial pressure, unloading ratio, and collapse completed-ratio. At a constant collapse-completed ratio, the remnant collapse coefficient significantly decreases with the decreasing unloading ratio; at a constant unloading ratio, the remnant collapse coefficient increases with a decreasing collapse-completed ratio. Decreasing unloading and collapse-completed ratios decreased the loess collapse potential with an initial pressure that exceeds the threshold value. Finally, an unloading collapse deformation calculation of loess was prepared to analyze practical project problems of loess based on the unloading collapse test.